Exploring an Immunomodulatory Role of Homoeopathy (Homoeopathy for All, 2025)
The immune system is a complex  network responsible for maintaining  the body’s defence against  pathogens and internal imbalances.  Homeopathy, a system of medicine  founded on the principle of "similia  similibus curentur" (like cures like),  offers a holistic approach to immune  modulation. Rather than directly  stimulating immune function,  homeopathy aims to restore  internal balance by addressing the  individual's physical, emotional, and  energetic state. This article explores  the conceptual basis of immune  health in homeopathy, clinical  applications in both acute and  chronic conditions, and the current  state of scientific evidence.
Keywords: immune; system; complex; network; responsible; maintaining